Data replication scheme for neighbor replication on grid - Wan Suryani Wan Awang (Fakulti Sains dan Teknologi, 2011)
In today's Internet world, the thirst for a reliable data across Web Server Cluster (WSC) is very crucial. WWW applications such as financial transactions, distant learning, e-commerce and e-business are generally require non-stop services. The explosively increasing of the internet users and accesses consequently contribute to this demand for data availability and reliability.